EFEK FRAKSI LARUT AIR EKSTRAK ETANOL 50% KEMUNING (Murraya paniculata (L.) Jack) TERHADAP BERAT BADAN TIKUS BETINA DIET LEMAK TINGGI - Suwijiyo Pramono; Agung Endro Nugroho; Crisna Wardhani (Universitas Islam Indonesia, 2004)
ABSTRACTObesity is considered as a health problem that can promote the risks of getting disease, beingnot active and death. In some developing countries, many traditional therapies are applied for somediseases, including obesity. Kemuning (Murraya paniculata (L.) Jack) has been commonly knownas slimming potion. In present, kemuning leaf is used as ingredient of traditional medicine formula,indicated as slimming potion. Former researcher mentioned that 30% ethanol-bemusing extract hadbeen able to reduce trigliserid content in the blood reduce cholesterol content in blood serum ofmale Wistar furrow white rat (Rattus norvegicus). This research is proposed to examine the effect ofwater soluble fraction of 50% ethanol-kemuning extract to female Wistar furrow white rat bodyweight which given high fat diet and to compare the effect with anorextica (mazindol). Testedanimal are divided into 6 groups, each group contain 5 rats. Group I as negative control is given0,5% CMC Na solution. Group II as positive control is given 0,27 mg/kgBody Weight mazindolsuspension. Group III is given 50% ethanol-kemuning extract suspension with 475 mg/kg BWdosage. Group IV is given watersoluble fraction suspension of kemuning extract dosage I that is145 mg/kgBW. Group V is given watersoluble fraction suspension of kemuning extract dosage IIthat is 295 mg/kgBW. Group VI is given dose III that is 585 mg/kgBW. The suspension is givenorally with repeated dosage. Data collected are the increase of body weight, woof consumption anddrinking consumption. Body weight and woof consumption increases are analyzed by one-wayAnava with 90% significancy level. Research result shows that water soluble fraction of 50%ethanol-kemuning extract with 585 mg/kgBW dosage and positive control (mazindol) are able toobstruct rat body weight increase significancy (p < 0,10) compared to negative control group.Keys word : Murraya paniculata (L.) Jack, obesity, antiobesity